Cardiovascular events after ischemic stroke in young adults: A prospective follow-up study. (17th May 2016) - Aarnio, Karoliina; Siegerink, Bob; Pirinen, Jani; Sinisalo, Juha; Lehto, Mika; Haapaniemi, Elena; Nave, Alexander-Heinrich; Kaste, Markku; Tatlisumak, Turgut; Putaala, Jukka
Abstract : Objectives: To study the long-term risk of recurrent cardiac, arterial, and venous events in young stroke patients, and whether these risks differed between etiologic subgroups. Methods: The study population comprised 970 patients aged 15–49 years from the Helsinki Young Stroke Registry (HYSR) who had an ischemic stroke in 1994–2007. We obtained follow-up data until 2012 from the Finnish Care Register and Statistics Finland. Cumulative 15-year risks were analyzed with life tables, whereas relative risks and corresponding confidence intervals (CI) were based on hazard ratios (HR) from Cox regression analyses. Results: There were 283 (29.2%) patients with a cardiovascular event during the median follow-up of 10.1 years (range 0.1–18.0). Cumulative 15-year risk for venous events was 3.9%. Cumulative 15-year incidence rate for composite vascular events was 34.0 (95% CI 30.1–38.2) per 1, 000 person-years. When adjusted for age and sex, patients with an index stroke caused by high-risk sources of cardioembolism had the highest HR for any subsequent cardiovascular events (3.7; 95% CI 2.6–5.4), whereas the large-artery atherosclerosis group had the highest HR (2.7; 95% CI 1.6–4.6) for recurrent stroke compared with patients with stroke of undetermined etiology. Conclusions: The risk for future cardiovascular events after ischemic stroke in young adults remains high for years after the index stroke, in particular when the index stroke is caused by high-risk sources of cardioembolism or large-artery atherosclerosis.